PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA PENERBANGAN TEMPUR TNI DALAM PELAKSANAAN OPERASI GABUNGAN - Asri Efendi Rangkuti; Ansori; Agustinus Gogot Winardi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
The success of an organization, including the TNI in joint operations, is greatly influenced by various factors, one of which is Human Resources (HR). HR is the main driver in organizational dynamics, because the role and contribution of humans is very vital in achieving common goals. The quality of human resources, especially for combat pilots, is greatly influenced by educational background. With education at the D4 level and a fairly high class, combat pilots are expected to have comparable competence. However, variations in pilot education can result in different levels of competency. Therefore, consistent training and education standards are necessary to ensure that all pilots can operate effectively and efficiently in their duties. The research aims to discuss the influence of Competency on the Performance of TNI Combat Aviation Soldiers; the influence of training on the performance of TNI combat aviation soldiers; and the influence of Competency and Training together on the Performance of TNI Combat Aviation Soldiers. The research method uses quantitative, with the object studied being the influence of competency and training on soldier performance, with competency (X1) and training (X2) as independent variables, and soldier performance (Y) as the dependent variable. The research results show that there is a significant influence between Competency on Soldier Performance; There is a significant influence between Training on Soldier Performance and Competency and Training simultaneously has a significant influence on the Performance of TNI Combat Pilot Soldiers.